Population red blood cell folate concentrations for prevention of neural tube defects: bayesian model - MOLLOY, ANNE (My University, 2014)
OBJECTIVE: To determine an optimal population red blood cell (RBC) folate concentration for the prevention of neural tube birth defects. DESIGN: Bayesian model. SETTING: Data from two population based studies in China. PARTICIPANTS: 247,831 participants in a prospective community intervention project in China (1993-95) to prevent neural tube defects with 400 μg/day folic acid supplementation and 1194 participants in a population based randomized trial (2003-05) to evaluate the effect of folic acid supplementation on blood folate concentration among Chinese women of reproductive age. INTERVENTION: Folic acid supplementation (400 μg/day). MAIN OUTCOME MEASURES: Estimated RBC folate concentration at time of neural tube closure (day 28 of gestation) and risk of neural tube defects. RESULTS: Risk of neural tube defects was high at the lowest estimated RBC folate concentrations (for example, 25.4 (95% uncertainty interval 20.8 to 31.2) neural tube defects per 10,000 births at 500 nmol/L) and decreased as estimated RBC folate concentration increased. Risk of neural tube defects was substantially attenuated at estimated RBC folate concentrations above about 1000 nmol/L (for example, 6 neural tube defects per 10,000 births at 1180 (1050 to 1340) nmol/L). The modeled dose-response relation was consistent with the existing literature. In addition, neural tube defect risk estimates developed using the proposed model and population level RBC information were consistent with the prevalence of neural tube defects in the US population before and after food fortification with folic acid. CONCLUSIONS: A threshold for "optimal" population RBC folate concentration for the prevention of neural tube defects could be defined (for example, approximately 1000 nmol/L). Population based RBC folate concentrations, as a biomarker for risk of neural tube defects, can be used to facilitate evaluation of prevention programs as well as to identify subpopulations at elevated risk for a neural tube defect affected pregnancy due to folate insufficiency.
PUBLISHED
Keywords: neural tube defect; neural tube defect; International Development